Interference in Japanese Learning by First-Year Students of Hospitality Department in State Polytechnic Of Bali - Harisal Harisal (Universitas Diponegoro, 2021)
The second-language learning process is often constrained by the influence of mother tongue or first language-Acquisition learners, which is called interference. Interference is principal language irrelevance in bilingual due to one or more language to be introduced or Speech Communication. Based on its phenomenon, students of State Polytechnic of Bali are considered passive interference learners, putting their mother tongue (Javanese and Balinese) elements and Indonesian Language in Japanese consciously or intuitively. This study aims to disclose the type of interference by the hospitality program students for those studying Japanese in State Polytechnic of Bali and explain its factors. The method used is Descriptive Qualitative, which is concerned with taking document field notes and literature Review to represent the real phenomenon of passive Interference types. The population in this study were all students in State Polytechnic of Bali in Japanese class. In contrast, the sample was taken from the results of purposive sampling based on their 100% attendance. There were about 65 first-year or second Semester students in Japanese Class and showed their Interferences. The study results showed that about 75 Passive Interference has commonly occurred in grammatical cases, such as phonetics, morphology, and syntax. Moreover, the occurrence factors of Passive Interference are distinctive Phonetic Features, The Language pattern differences between Mother Tongues (Local Languages) – Japanese, and lack of Japanese Language Proficiency skills and its dictions.